NEW TRENDS IN THE STATE-TO-STATE PHOTODISSOCIATION DYNAMICS OF H2O(A) - Brouard, M; Langford, S; Manolopoulos, D (American Inst of Physics, 1994)
The focus of this paper is on the measurement and interpretation of the photofragment rotational distributions arising from the 282 nm photodissociation of water initially prepared in the third and fourth OH stretching overtone and stretch-bend combination levels. Through photolysis the distributions generated of the third and fourth overtone levels are found to differ from those obtained previously. Model Franck-Condon calculations provide a qualitative rationale for both the present data and the previous experimental results.